PERBEDAAN CAREER DECISION MAKING SELF-EFFICACAY (CDMSE) PADA MAHASISWA AKHIR YANG BERORGANISASI DAN TIDAK BERORGANISAI - Jelita Elfidawati Silitonga; Hotpascaman Simbolon (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The transition from university to the workforce is shaped not only by students' academic achievement but also by their confidence in making career-related decisions. Differences in learning experiences throughout higher education, including participation in student organizations, are assumed to contribute to the development of Career Decision-Making Self-Efficacy (CDMSE). Accordingly, this study compared the level of CDMSE between final-year students who actively participated in student organizations and those who did not at HKBP Nommensen University Medan. A quantitative comparative design was employed, involving 300 participants selected through purposive sampling, consisting of 150 students who were actively engaged in student organizations and 150 students with no organizational involvement. Data were collected using a valid and reliable Career Decision-Making Self-Efficacy scale and analyzed using an Independent Samples t-test. The findings revealed a statistically significant difference in CDMSE between the two groups (t = 2.202; p = 0.028). Students who actively participated in student organizations demonstrated a higher mean CDMSE score than their non-participating counterparts, indicating that organizational experiences are associated with stronger confidence in career decision-making. Nevertheless, the findings also suggest that CDMSE is shaped not solely by organizational involvement but by a broader range of learning experiences acquired throughout university. These results provide empirical evidence supporting the development of more inclusive career development services to better prepare students for the transition into the professional workforce. ABSTRAK Perjalanan mahasiswa menuju dunia kerja tidak hanya ditentukan oleh pencapaian akademik, tetapi juga oleh keyakinan mereka dalam menetapkan pilihan karier. Perbedaan pengalaman selama menjalani pendidikan tinggi, termasuk keterlibatan dalam organisasi kemahasiswaan, diduga berkontribusi terhadap pembentukan Career Decision-Making Self-Efficacy (CDMSE). Atas dasar tersebut, penelitian ini membandingkan tingkat CDMSE antara mahasiswa tingkat akhir yang aktif berorganisasi dan mahasiswa yang tidak mengikuti organisasi di Universitas HKBP Nommensen Medan. Penelitian menerapkan pendekatan kuantitatif dengan desain komparatif dan melibatkan 300 responden yang dipilih menggunakan teknik purposive sampling, terdiri atas 150 mahasiswa aktif berorganisasi dan 150 mahasiswa yang tidak berorganisasi. Pengumpulan data dilakukan menggunakan skala Career Decision-Making Self-Efficacy yang telah memenuhi kriteria validitas dan reliabilitas, kemudian dianalisis melalui Independent Samples t-test. Analisis menunjukkan adanya perbedaan CDMSE yang signifikan antara kedua kelompok (t = 2,202; p = 0,028). Rerata skor mahasiswa yang aktif berorganisasi lebih tinggi dibandingkan kelompok yang tidak berorganisasi, mengindikasikan bahwa pengalaman organisasi berkaitan dengan meningkatnya keyakinan dalam mengambil keputusan karier. Meskipun demikian, temuan ini juga memperlihatkan bahwa pembentukan CDMSE tidak hanya bersumber dari aktivitas organisasi, melainkan dipengaruhi oleh berbagai pengalaman belajar yang diperoleh selama masa studi. Hasil penelitian memberikan dasar empiris bagi perguruan tinggi untuk mengembangkan layanan pengembangan karier yang lebih inklusif guna mendukung kesiapan mahasiswa menghadapi transisi ke dunia kerja.